THE ANALYSIS OF DIGITAL PAYMENT USAGE INTENTION FROM TPB AND TAM PERSPECTIVE - Fellicia liem; Jean Richard Jokhu (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This research has the purpose to analyze the factors that cause digital payment usage intention, the factors that being used in this research is security, perceived usefulness, perceived ease of use, trust, subjective norms, and attitude then find out the impact of the security toward usage intention, perceived usefulness toward usage intention, perceived ease of use toward usage intention, trust toward usage intention, subjective norms toward usage intention, attitude toward usage intention, and the simultaneous impact from all of the variables toward usage intention The methodology that use in this study is quantitative approach hence it will use the questionnaire as media to gathering the primary data. This study used 300 sample data of Indonesia citizen for being analysis using validity and reliability test, multiple regression analysis, T-test and F-test the result is: security, perceived usefulness, perceived ease of use, trust, subjective norms and attitude give significant impact to the digital payment usage intention. However, perceived usefulness did not give significant impact toward digital payment usage intention (it give very low impact on digital payment usage intention). The result from multiple regression analysis R2 shows the result 0.481 which mean all of the factors that choose to analyze in this research influence as big as 48.2% toward usage intention.